Reframing the Monolingual ’Family Romance’: Metaphors and Linguistic Kinships in Jhumpa Lahiri’s In Other Words - Hillebrand, Maya (Satura, 2022)
The faculty of language – expressing, reading, and understanding complex sentences and words – is one of the key features of humanity and human culture. Paradoxically, languages do not just unite humans in this ability, but can also set us apart from one another or even create divisions within us if we speak more than one language. Such is the case for American novelist and short story writer Jhumpa Lahiri, who grew up bilingually with English and Bengali. In her autobiographical work, In Other Words, she describes her relationship with the two languages and the changes in her linguistic identity when she adopts a third language and moves to Rome to learn Italian. Even though she had established herself as an Anglophone writer, Lahiri began to write exclusively in this new and foreign tongue during her time in Italy. With In altre parole (In Other Words), she published her first Italian book which was not just a documentation of her linguistic journey but, first and foremost, a testament of her love for Italian. In an interview with Mondiaal Nieuws, Lahiri explained the value of multilingualism, saying that “someone who speaks more than one language […] knows that there is more than a single way to be human” while “[someone] who lives in a monolingual universe, looks at the world through one eye only. You lack perspective” (Goris).